Synergistic effect of bath-ultrasonication and heating treatments on two-steps treatment of brewers’ spent grain - Naibaho, Joncer; Bobak, Łukasz; Wojdyło, Aneta; Korzeniowska, Małgorzata; Lu, Yuyun; Yang, Baoru (Elsevier, 2025)
The study aimed to evaluate the chemical composition, antioxidant activity and techno-functionality of brewers’ spent grain (BSG) treated with two-steps treatment involving 5, 15, and 25 min bath-ultrasonication (USB) continued with autoclave (AH) at 90, 110, and 130 °C and/or water-bath (CWH) at 80, 90, and 100 °C. The two-steps treatments slightly affected the water- and oil-holding capacity and extractable fat content. Most of the two-steps treatments increased the amount of flavan-3-ols and phenolic acids, up to 4 times higher compared to its control. The two-steps treatment involving CWH had no significant (p > 0.05) impact on fat content, antioxidants and techo-functionality of BSG. Up to 15 min USB increased the poly-unsaturated fatty acids and lowered the amount of saturated fatty acids. In conclusion, the two-steps treatment consists of USB (up to 15 min) continued with AH and CWH increased the amount of nutritional-related chemical composition such as UFA and phenolic acids as well as antioxidant activity of BSG.